Pengaruh Budaya Hukum Terhadap Penegakan Hukum Tindak Pidana Korupsi Dalam Dunia Pendidikan Di Indonesia - Surbakti, Anton Diary S.; Lubis, Aldira Ardiansyah; Zebua, Johan Teguh (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to determine: (1) the rules for the enforcement of corruption in Indonesia, (2) the influence of the culture of rules on the enforcement of the rules for corruption in Indonesia, (3) the efforts of educational forums to eradicate corruption in Indonesia The procedure for collecting and collecting data used in this research is through a literature study/documentary study, using relevant regulatory materials, collecting materials that will be used in this research, conducting searches to find relevant regulatory materials. using Legal Culture and Criminal Acts of Corruption in efforts to overcome Corruption Crimes in global education in Indonesia. Through this data collection technique, it is necessary to find a concept that can answer the news of the rules in this study. Based on the output of this study, it appears that the eradication of corruption by the government has not resulted in the required output. The complexity of the fight against corruption in Indonesia is apparently not relatively solved by relying on preventive and investigative tactics, but also educative tactics.